2015
DOI: 10.1175/bams-d-14-00122.1
|View full text |Cite
|
Sign up to set email alerts
|

Key Conclusions of the First International Urban Land Surface Model Comparison Project

Abstract: The First International Urban Land Surface Model Comparison was designed to identify three aspects of the urban surface–atmosphere interactions: 1) the dominant physical processes, 2) the level of complexity required to model these, and 3) the parameter requirements for such a model. Offline simulations from 32 land surface schemes, with varying complexity, contributed to the comparison. Model results were analyzed within a framework of physical classifications and over four stages. The results show that the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
109
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 72 publications
3
109
0
1
Order By: Relevance
“…However, a sensitivity study shows that 519 an amount of 0.035 mm each hour gives a modelled median of β that is close to that observed (Fig. The initial soil moisture conditions have been shown previously to be critical for modelling sensible 582 and latent heat fluxes in urban environments (Best and Grimmond, 2015a). Hence it requires only a small amount of water to be added each hour to explain the observed β, 521 so it is possible that such a source of water is responsible for the observed evaporation.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…However, a sensitivity study shows that 519 an amount of 0.035 mm each hour gives a modelled median of β that is close to that observed (Fig. The initial soil moisture conditions have been shown previously to be critical for modelling sensible 582 and latent heat fluxes in urban environments (Best and Grimmond, 2015a). Hence it requires only a small amount of water to be added each hour to explain the observed β, 521 so it is possible that such a source of water is responsible for the observed evaporation.…”
supporting
confidence: 62%
“…Typically these models are designed to 47 represent the energy balance of the various facets that make up an idealized urban canopy. Indeed, the first 57 international urban model comparison experiment (PILPS-Urban) concluded that for the two urban 58 sites considered in the study (Vancouver and Melbourne), models that included a representation of 59 vegetation performed much better in simulating the sensible (QH) and latent heat (QE) densities than 60 models that neglected it (Grimmond et al, 2010, 2011, Best and Grimmond, 2013, 2015a. Whilst this may be a good 52 representation of the central downtown areas of major cities, this design alone (i.e., without a 53 representation of vegetation) does not capture the influence of vegetation present in many street 54 canyons and abundant in the suburbs of many cities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Loridan et al, 2013;Bohnenstengel et al, 2011;Kondo et al, 2005;Masson et al, 2000) that aimed to more accurately represent the complex processes that occur in these environments. The inaccuracies have been well documented (Best and Grimmond, 2015) and there have been studies done that have utilized parameterization techniques and different model schemes to try and get better agreement between the model and the observations (e.g. Loridan and Grimmond, 2012;Loridan et al, 2010).…”
Section: Pbl and Lsm Scheme Sensitivity And Improving Simulations Ovementioning
confidence: 99%
“…It is possibly because nighttime SUHI mainly resulted from the higher thermal admittance of building materials in urban areas than rural areas, which does not change significantly across seasons [29]. Another key factor affecting nighttime SUHII is anthropogenic heat emissions [67,68] from appliances, transportation systems and infrastructures, factories and other human activities, which exist all year around.…”
Section: Possible Mechanisms Of Seasonal Suhii Variationsmentioning
confidence: 99%